PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT DAN JOB SATISFACTION TERHADAP EMPLOYEE ENGAGEMENT PADA KARYAWAN KOPERASI “TKBM” PELABUHAN TANJUNG PERAK - Devi Berliana Shanty; Rini Nurahaju; Tri Budi Marwanto (Fakultas Psikologi Universitas Hang Tuah, 2022)
This study aims to determine the effect of perceived organizational support partially on employee engagement, the effect of partial job satisfaction on employee engagement, and the effect of perceived organizational supportand job satisfaction jointly on employee engagement of the employees of the Tanjung Perak Port Cooperative ''TKBM''. This study uses a quantitative approach with survey research methods. Psychological measuring tools use 3 scales, namely employee engagement, perceived organizational support, and job satisfaction. The total population in this study was 75 people. This study uses a saturated sampling technique. The results of this study indicate that 1) there is a partial effect of perceived organizational support on employee engagement in the employees of the Tanjung Perak Port ''TKBM'' there is a partial effect of job satisfaction on employee engagement for employees of the Tanjung Perak Port “TKBM” Cooperative. There is a joint effect of perceived organizational supportand job satisfaction on employee engagement of the Tanjung Perak Port ''TKBM'' Cooperative employees.